Eight-year performance evaluation of a field-scale zeolite permeable reactive barrier for the remediation of ammonium-contaminated groundwater. (August 2022) - Chen, Linpeng; Wang, Congyi; Zhang, Chong; Zhang, Xiao; Liu, Fei
Abstract: Groundwater, which is one of the main sources of water for cities in northern China, is strongly influenced by surface water, particularly in riverside areas. To remediate ammonium-contaminated groundwater in riverside source fields, a zeolite permeable reactive barrier (PRB) was constructed in Shenyang, China. In this study, groundwater monitoring data from 2012 to 2019 were collected, and an eight-year performance evaluation of the zeolite PRB was conducted with respect to ammonium-nitrogen (NH4 + -N) treatment and the corresponding removal mechanism. Groundwater monitoring results showed that NH4 + -N removal was divided into stable (2012–2015), semi-stable (2016–2017) and unstable stages (2018–2019). During the stable stage, the NH4 + -N concentration in the monitoring well located in the hydraulic down-gradient of the PRB decreased below the national standard limit of 0.5 mg/L with a higher removal efficiency (52%–97%), which was mainly owing to the strong adsorption capacity of the zeolite for NH4 + -N. During the semi-stable stage, although the NH4 + -N concentration in the down-gradient monitoring well of the PRB fluctuated greatly (0.18 mg/L−1.45 mg/L), the PRB system maintained a relatively high NH4 + -N removal efficiency (16%–72%) because of strong nitrification. However, the zeolite in the PRB reached adsorption saturation after 2016, which resulted in NH4 + -N desorption when less NH4 + -N-contaminated groundwater flowed through the PRB. Then, a NH4 + -N concentration in the down-gradient monitoring well of the PRB exceeding 0.5 mg/L has been observed during the unstable stage. Gene analysis results provided evidence that stronger denitrification and weaker nitrification capacity existed in the PRB system in 2018. The weaker nitrification was not enough to convert all the desorbed NH4 + -N into NO3 − -N, which led to an increase in the down-gradient NH4 + -N concentration of the PRB from 2018 to 2019. Overall, time-dependent decay in the PRB performance for NH4 + -N removal was noticeable after operating for 4–5 years and thus it is necessary to consider and conduct subsequent microbially mediated zeolite regeneration in the zeolite PRB. Highlights: An eight-year performance evaluation of the field-scale PRB was conducted. Stable, semi-stable and unstable stages for NH4 + -N removal were identified. NH4 + -N was removed through adsorption onto zeolites and biological nitrification. Microbially mediated zeolite regeneration is necessary after 4–5 years operation.